Delayed Diagnosis of Giant Cell Arteritis in the Setting of Isolated Lingual Necrosis. Issue 12 (June 2019) - DeBord, Logan Christopher; Chiu, Ilene; Liou, Nelson Eddie
Background: Lingual necrosis is a rare complication of giant cell arteritis (GCA). Methods: A 77-year-old woman presented for treatment of a painful and discolored tongue, odynophagia, and dehydration refractory to antimicrobials over 2 weeks. An extensive, well-demarcated necrotic area was visualized on the anterior tongue upon admission. Leukocytosis, thrombocytosis, and elevated erythrocyte sedimentation rate were present. Computed tomography angiogram of the head and neck revealed an undulated-beaded appearance of the distal internal carotid arteries and vertebral arteries bilaterally. Results: High-dose intravenous steroids were initiated for suspected vasculitis. Temporal artery biopsy confirmed the diagnosis of GCA. The patient's condition improved and the anterior tongue was well healed at 1 month follow-up. Conclusions: An atypical presentation of GCA (eg, isolated lingual necrosis) risks a delay in diagnosis and increased morbidity. Any patient above the age of 50 years presenting with tongue necrosis, in the absence of known cause, should undergo expedited workup for GCA.